Water savings from urban infrastructure improvement and wastewater reuse: evidence from Jordan. Issue 6 (2nd November 2021) - Jeuland, Marc; Moffa, Michelle; Alfarra, Amani
ABSTRACT: Jordan is extremely water scarce, making careful water resources planning and management essential. This study considers the water-supply-enhancing effects of a significant urban investment, the Jordan Compact, that supports Jordan's national objective of enhanced water reuse and efficiency. Analysis using a Water Evaluation and Planning model suggests that the Compact generated substantial water savings (averaging 7–8 MCM/y), easing shortages in urban Zarqa and Amman, as well as among irrigators in the Jordan Valley. Though the impacts appear to have fallen short of pre-Compact expectations, policy makers should consider similar improvements to ease water constraints, while incentivizing efficient water utilization.